Clinicopathological study of 74 palatal pleomorphic adenomas - Yang-Che Wu (Journal of the Formosan Medical Association, 2016)
Pleomorphic adenoma (PA) is the most common salivary gland tumor and the palate is the most common intraoral site for PA. This study aimed to present the clinicopathological features of a series of 74 palatal PAs. Methods: Seventy-four palatal PAs were collected from 1993 to 2009. The clinical and histopathological features of these 74 PAs were reviewed and analyzed. Results: The 74 palatal PA patients showed a marked female predilection (49:25, ∼2:1) and were nearly evenly distributed from the 3rd to 8th decades of life with a mean age of 47 years. All palatal PAs were treated by wide surgical excision and recurrence was noted in one PA. Histopathologically, there were 47 classic and 27 cellular PAs. Of the 74 PAs, 12 were completely encapsulated, 40 partially encapsulated, and 22 nonencapsulated. The duct-like structures and myxoid stroma were more or less found in every palatal PA. Plasmacytoid myoepithelial cell, clear cell, squamous epithelial nest, keratin pearl, hyalinized stroma, osteoid area, and chondroid area were found in 50, 19, 29, 19, 49, eight, and six PAs, respectively. Conclusion: We conclude that the palatal PA patients show a prominent female predilection (2:1) and are nearly evenly distributed from 20 years to 79 years of age. Plasmacytoid myoepithelial cell is the most characteristic type of tumor cell in PAs. Wide surgical excision is treatment of choice for PAs. Although ∼84% of palatal PAs are partially or nonencapsulated, recurrence of the lesion is rarely encountered after total surgical removal of the tumors.